2021
DOI: 10.1111/joa.13545
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and angiogenic profiles of the palatal process of the maxilla and the palatal process of the palatine bone

Abstract: Hard palate consists anteriorly of the palatal process of the maxilla (ppmx) and posteriorly of the palatal process of the palatine (ppp). Currently, palatal osteogenesis is receiving increasing attention. This is the first study to provide an overview of the osteogenesis process of the mouse hard palate. We found that the period in which avascular mesenchymal condensation becomes a vascularized bone structure corresponds to embryonic day (E) 14.5 to E16.5 in the hard palate. The ppmx and ppp differ remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In our previous study, TRAP-positive osteoclasts were first reported at PPMXA, PPMXP and PPP at E18.5, E17.5 and E16.5, respectively. 6 Investigating the spatiotemporal expression of CSF1R in the embryonic palate, we found that CSF1R was significantly upregulated at E16.5, E15.5 and E14.5 in PPMXA, PPMXP and PPP, respectively. Remarkably, these time points coincided with the initial two days when TRAP-positive osteoclasts were detectable (data pending publication).…”
Section: Csf1r Is An Essential Signal For Palatal Osteoclastogenesismentioning
confidence: 89%
See 2 more Smart Citations
“…In our previous study, TRAP-positive osteoclasts were first reported at PPMXA, PPMXP and PPP at E18.5, E17.5 and E16.5, respectively. 6 Investigating the spatiotemporal expression of CSF1R in the embryonic palate, we found that CSF1R was significantly upregulated at E16.5, E15.5 and E14.5 in PPMXA, PPMXP and PPP, respectively. Remarkably, these time points coincided with the initial two days when TRAP-positive osteoclasts were detectable (data pending publication).…”
Section: Csf1r Is An Essential Signal For Palatal Osteoclastogenesismentioning
confidence: 89%
“…[4] Our previous study first described TRAP-positive osteoclasts detected at the embryonic palatal bone. 6 Studies of embryonic osteoclasts have focused on long bones, and to the best of our knowledge, only Kawata T has thus far described osteoporotic (op/op) mice exhibiting immature fusion of the midpalatal suture due to a reduction in osteoclasts without further detailed investigations. 7 Subsequently, a Csf1 inactivating mutation was found in these mice, which are now termed Csf1op/op mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since scaffold porosity and microporosity are the same for both scaffolds, a lower O 2 -concentration in Fil050G samples appears unlikely and additional factors might have induced EREG expression. Moreover, NR4A1 and FGF18 , also upregulated in Fil050G samples, have links to angiogenesis/osteogenesis-related factors [ 53 , 54 , 55 ]. Furthermore, ACVRL1 , C-type lectin domain family 14 member A ( CLEC14A ) [ 56 ], and Nitric oxide synthase endothelial ( NOS3 ) [ 57 ] possess angiogenic/vasculogenic potential within the bone healing process [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, distinct gene expression patterns along the antero-posterior axis of the secondary palate were generally recognized. For further research, we described morphogenesis and heterogeneity in the osteogenic and angiogenic gene profiles of the PPMX and PPP in a previous study 9 .…”
Section: Introductionmentioning
confidence: 99%